Preparation and Antibacterial Activity of Ag/Chitosan Complex - Yang, Benhong; Li, Meng; Wu, Yun; Deng, Chonghai; Yu, Xuelian; Zhang, Hui (Asian Journal of Chemistry, 2012)
While retaining the original activity of chitosan (CTS), water-soluble carboxymethylated chitosan (CM-CTS) was first synthesized via the carboxymethylation of chitosan with chloroacetic acid and then complexed with silver ions to form stronger antimicrobial agent (Ag/CM-CTS). FTIR was employed to characterize and confirm the structures of each product. Antimicrobial tests show that Ag/CM-CTS has much higher antimicrobial activity than both CTS and CM-CTS against ether E. coli or B. subtilis. The minimum inhibitory concentrations of Ag/CM-CTS against E. coli and B. subtilis are 0.1 and 0.2 mg/mL, respectively.